On the Multimodal Path to Language: The Relationship Between Rhythmic Movements and Deictic Gestures at the End of the First Year - Murillo, Eva; Montero, Ignacio; Casla, Marta (Frontiers in Psychology, 2021)
The aim of this study is to analyze the relationship between rhythmic movements and deictic gestures at the end of the first year, and to focus on their unimodal or multimodal character. We hypothesize that multimodal rhythmic movement performed with an object in the hand can facilitate the transition to the first deictic gestures. Twenty-three children were observed at 9 and 12 months of age in a naturalistic play situation with their mother or father. Results showed that rhythmic movements with objects in the hand are a frequent behavior in children’s repertoires. Rhythmic behaviors tend to decrease from 9 to 12 months, specifically when they are unimodal. Multimodal rhythmic behavior production at 9 months is positively related with proximal deictic gestures three months later. Multimodal rhythmic movements are not directly related to distal deictic gestures, but are indirectly related via proximal deictic gestures. These results highlight the relevance of multimodal behaviors in the transition to the use of early gestures, and can be considered as a transitional phenomenon between the instrumental action and early communicative gestures.